Conditions et processus menant à des changements à la suite d’interventions en santé et en sécurité du travail : l’exemple d’activités de formation - Geneviève Baril-Gingras; Marie Bellemare; Jean-Pierre Brun (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article deals with the conditions and processes that lead to changes following occupational health and safety interventions, with training activities being used as an example. Observations and interviews were conducted during four training interventions carried out by advisors from joint OHS sector-based associations. Three aspects of the context influence the changes: the previous degree of development of prevention activities; the presence of “relay” actors; and the presence of favourable issues. Previous collaboration with the prevention organization contributes to the presence of the first two, suggesting the relevance of sustained follow-up by the prevention organization. Different strategies are used to develop these capacities and to raise favourable issues. Different processes leading to changes were observed: a change in the workers’ perception of their capacity to take action; legitimization of their action on risks; sharing of prevention-related experience; and a collective problem-solving process.